Antireflection ln2O3 coatings of self-organized TiO2 nanotube layers prepared by atomic layer deposition - Macák, Jan M.; Přikryl, Jan; Sopha, Hanna Ingrid; Střižík, Lukáš (Wiley-VCH, 2015)
We report on the uniform anti-reflection coating of TiO2 nanotube layers with a secondary material – indium trioxide (In2O3) – by Atomic Layer Deposition (ALD). We provide for the first time the detailed evidence of the ALD deposited coating inside nano-tubes for three different tube layers with aspect ratio up to ≈80, which is so far the highest aspect ratio reported for ALD-processed self-organized anodic TiO2 nanotubes. We show that uniform In2O3 coating of the nanotubes strongly influences the overall reflectance of the layers due to intrinsic properties of In2O3.
Keywords: TiO2 nanotubes; In2O3; antireflection coating; atomic laser deposition; light absorption